The Ideal Canine Companion: Re-Exploring Australian Perspectives on Ideal Characteristics for Companion Dogs - Emma S. Power; Jessica Dawson; Pauleen C. Bennett (Animals)
Defining the ideal characteristics of canine companions is imperative to those seeking to improve human–dog relationships. Previous investigations into the preferred traits of companion dogs were conducted before substantial recent events, such as the rise of social media and the COVID-19 pandemic, which altered human lifestyles and potentially affected canine preferences and owner satisfaction. This study surveyed Australian adults (n = 337) online to assess these shifts. The ideal dog was characterised as medium-sized, with a short- low- or non-shedding coat, and acquired as a puppy from a shelter/rescue. Desired traits included being affectionate, healthy, non-aggressive, safe with children, housetrained, non-destructive when alone, and not prone to escaping. Principal Component Analysis identified five factors: ‘calm and obedient’, ‘inhibitory control’, ‘energy and drive’, ‘non-aggressive and safe’, and ‘affectionate and healthy’. Demographic variables of age, gender, perceived income, and household children influenced preferences. No significant differences in owner satisfaction with behaviour were observed between dogs acquired during versus outside the pandemic. The findings align with prior Australian research, suggesting enduring stability in preferences for the ideal companion dog. These insights offer valuable guidance for breeders, prospective owners, and policymakers to reduce dog relinquishment and improve human–dog relationships.